Origin : a novel - Brown, Dan. (New York : Anchor Books, 2017)
Robert Langdon, Harvard professor of symbology and religious iconology, arrives at the ultramodern Guggenheim Museum Bilbao to attend a major announcement - the unveiling of a discovery that "will change the face of science forever." The evening's host is Edmond Kirsch, a 40-year-old billionaire and futurist whose dazzling high-tech inventions and audacious predictions have made him a renowned global figure. Kirsch, who was one of Langdon's first students at Harvard two decades earlier, is about to reveal an astonishing breakthrough...one that will answer two of the fundamental questions of human existence. As the event begins, Langdon and several hundred guests find themselves captivated by an utterly original presentation, which Langdon realizes will be far more controversial than he ever imagined. But the meticulously orchestrated evening suddenly erupts into chaos, and Kirsch's precious discovery teeters on the brink of being lost forever. Reeling and facing an imminent threat, Langdon is forced into a desperate bid to escape Bilbao. With him is Ambra Vidal, the elegant museum director who worked with Kirsch to stage the provocative event. Together they flee to Barcelona on a perilous quest to locate a cryptic password that will unlock Kirsch's secret.
Keywords: MYSTERY -- SUSPENSE -- THRILLER -- FICTION